Դավիթ Անհաղթը լեզվաբան - Լ. Գ. Բրուտյան (ՀՀ ԳԱԱ Հ. Աճառյանի անվ. լեզվի ինստիտուտ)
В статье рассматриваются лингвистические взгляды Давида Анахта. В частности, анализируются вопросы взаимоотношения языка и мышления, грамматики, синонимии, антонимии, терминологии, стилистики и некоторые другие в трудах великого средневекового мыслителя.In the paper, the linguistic views of David the Invincible are considered. In particular, the problems of interrelation of language and thought, of grammar, synonymy, antonymy, terminology, stylistics and some others in the works of the great medieval thinker are analysed.
Keywords: Լեզվաբանություն; Կենսագրություն